2019
DOI: 10.31083/j.jin.2019.03.193
|View full text |Cite
|
Sign up to set email alerts
|

Contingent negative variation for the periodicity of migraine attacks without aura

Abstract: Migraine is a primary neuropsychological disorder, although its etiology and pathogenesis are unknown. It has been reported that using contingent negative variation, the periodicity of migraine attacks is three days in adults. However, there is still a lack of relevant reports about the periodicity of migraine without aura in adults. Therefore, we investigated the changes of contingent negative variation in adults with migraine without aura from three to seven days after migraine attacks in order to provide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…In agreement with other studies using data of a reduced number of electrodes, young children showed only minor frontal negativity during orienting response (Jonkman et al, 2003;Segalowitz & Davies, 2004), i.e., activation of cortical areas related to the supplementary motor area (SMA) and anterior cingulate cortex (ACC) (Flores et al, 2009;Jonkman et al, 2003). The early frontal negativity stabilized during post-pubertal adolescence, reaching strength of activation comparable to adult subjects (Tian et al, 2019;Weisz et al, 2002). Furthermore, we observed a consistent shift in iCNV latencies, with midfrontocentral areas being recruited earlier in older subjects, suggesting a faster processing of the warning stimulus.…”
Section: Maturation Of Orienting Response (Early Contingent Negative ...supporting
confidence: 90%
“…In agreement with other studies using data of a reduced number of electrodes, young children showed only minor frontal negativity during orienting response (Jonkman et al, 2003;Segalowitz & Davies, 2004), i.e., activation of cortical areas related to the supplementary motor area (SMA) and anterior cingulate cortex (ACC) (Flores et al, 2009;Jonkman et al, 2003). The early frontal negativity stabilized during post-pubertal adolescence, reaching strength of activation comparable to adult subjects (Tian et al, 2019;Weisz et al, 2002). Furthermore, we observed a consistent shift in iCNV latencies, with midfrontocentral areas being recruited earlier in older subjects, suggesting a faster processing of the warning stimulus.…”
Section: Maturation Of Orienting Response (Early Contingent Negative ...supporting
confidence: 90%
“…On the other hand, only a smaller group of studies described the effects on the lCNV [36,39,59,88]. Finally, the other investigations did not reveal enhanced amplitudes in any of the CNV subcomponents [20,26,62,68]. Indeed, the most recent study in this field, conducted by Tian and colleagues (2019) [26], found no significant differences in the CNV components (eCNV, lCNV or total CNV) between patients with migraine and healthy individuals [26].…”
Section: Cnv Results In Adult Migraine Patientsmentioning
confidence: 92%
“…This finding has been linked to a potential deficit to habituate towards sensory events. By contrast, some investigations conducted in this field failed to observe differences in the CNV habituation between healthy people and migraine [26,45], or such differences arose in association with the intake of some types of medication (it will be explained in more detail later) [42,60,63].…”
Section: Cnv Results In Adult Migraine Patientsmentioning
confidence: 94%
See 2 more Smart Citations